Effect of Profitability on Stock Returns of Companies in the Food and Beverage Sector in Indonesia - Heru Prayitno, Yogo; Suryana; Apriliana, Tria; Edison, Acep (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to determine the effect of profitability with the variable Return on Equity on stock returns in food and beverage sector companies in Indonesia. The study was conducted using 18 companies as a sample using financial reports on manufacturing sub-food and beverage consumer goods. The research method used was purposive judgment sampling using multiple linear regression. The results of the study state that profitability using return on equity affects stock returns.